Ion beam measurement using Rogowski coils in a hundred of joules dense plasma focus device. (May 2016) - Jain, J.; Moreno, J.; Pavez, C.; Bora, B.; Inestrosa-Izurieta, M. J.; Avaria, G.; Soto, L.
Abstract: In present work an effort has been made to measure the ion beams generated during experiment with PF-400J plasma focus device, using an array of two Rogowski coils with time of flight analysis. It was found that the coils measure the signals of beam for a particular range of operating pressure. The beam signals were recorded at 20, 15, 12, 10, 9, 8, 7, 6 and 5 mbar filled pressure of hydrogen gas. The optimized pressure range for good plasma column formation for this device was found about 9 mbar. At 15 mbar no or very weak beam signals were observed by Rogowski coil which was kept relatively far from the top of the anode and at 20 mbar there were no beam signals observed in both of the coils. The calculated beam energy is found to have maximum value at 9 mbar of filled hydrogen gas pressure.